The Origin of Labour Camp Theme in A.I. Solzhenitsyn’s Works: from Poetry to The Gulag Archipelago - Nadezhda I. Glukhova; Nellya M. Shchedrina (Studia Litterarum)
In the present article A.I. Solzhenitsyn’s poetic works and The Gulag Archipelago are analyzed, their proximity and thematic kinship are revealed. The authors appeal to the creative history of these works, remark that poems and parts of the Archipelago are arranged according to a certain pattern. Both in poetry and prose, Solzhenitsyn reveals the path taken by Soviet convicts. Camps for political prisoners and I.V. Stalin’s death take significant place in his works. A.I. Solzhenitsyn is particularly interested in the unity of heroes with nature, communion with it as with an attribute of free people’s life. The writer claims that the camp may become a starting point for spiritual resurrection of a human being. Metaphorization as one of the artistic elements is used for the first time in lyrics to reveal the image of Russia. The authors conclude that the camp theme arose during Solzhenitsyn’s imprisonment and was first expressed in lyrics and the narrative poem Dorozhen’ka. The Gulag Archipelago was formed later not only from the personal experience of the author but also from numerous materials and evidence of eyewitnesses.